GERAKAN MAHASISWA PADA MASA ORDE LAMA: SUATU PERSPEKTIF HISTORIS - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2015)
The student movement in the post-independence as well as the Old Order ups and downs along with the socio-political atmosphere. During the revolutionary period students involved in the struggle for independence. While at the time of Liberal Democracy, student activism changed. At first they are more academic activism alone and free from political interests outside the university. But in the elections of 1955 university and college students have politicized, making it applicable conflict and discord. In the Guided Democracy period (1959-1965)increasing student political activity. Occurs strong government intervention against the university. In addition, the form is also the influence of leftist groups who cause strife and conflicts between student organizations. University of previously fragmented worse. These circumstances occur until 1965 when the Communist Party of Indonesia destroyed.